Insights into the metastatic bone marrow niche gained from fibronectin and β1 integrin transgenic mice - Wirth, Franziska; Zöller, Caren; Lubosch, Alexander; Schröder-Braunstein, Jutta; Wabnitz, Guido H.; Nakchbandi, Inaam (Neoplasia, 2024)
Tumor cells can migrate from a primary cancer and form metastases by localizing to niches within other organs including the bone marrow, where tumor cells may exploit the hematopoietic stem cell niche. The precise composition of the premetastatic and the hematopoietic niches and the degree of overlap between them remain elusive. Because the extracellular matrix protein fibronectin is expressed in the pre-metastatic lung microenvironment, we evaluated the implications of its loss, as well as those of loss of its primary receptor subunit, β1 integrin, in various bone marrow cell types both in breast cancer bone metastasis and hematopoiesis. Using eight transgenic mouse models, we established that fibronectin production by osterix-expressing marrow cells, or β1 integrin expression (on vav, mx, or leptin receptor expressing cells), affects MDA-MB-231 breast cancer cell numbers in the bone marrow. Additionally, we identified stromal subpopulations that modulate transmigration through blood vessel walls. Not the number of tumor cells, but rather the changes in the microenvironment dictated whether the tumor progresses. Furthermore, hematopoiesis, particularly myelopoiesis, was affected in some of the models showing changes in tumor homing. In conclusion, there is partial overlap between the pre-metastatic and the hematopoietic niches in the bone marrow. Moreover, we have delineated a cascade starting with fibronectin secreted by pre-osteoblastic cells, which potentially acts on β1 integrin in specific stromal cell subsets, thereby inhibiting the formation of new breast cancer lesions in the bone marrow. This work therefore sheds light on the role of various stromal cell subpopulations that influence tumor behavior and affect hematopoiesis.